2020
DOI: 10.1021/acsaem.0c01714
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Li6.75La3Zr1.75Ta0.25O12-Based Composite Solid Electrolytes Laminated on Anode and Cathode Surfaces for Anode-free Lithium Metal Batteries

Abstract: The low ionic conductivity, thermal stability and incompatibility of pellet-like solid-state electrolytes lead to low cycling performance in anode-free lithium metal batteries. Herein, we report an effective and feasible composite solid electrolyte-designing approach using the garnet (Li 6.75 La 3 Zr 1.75 Ta 0.25 O 12 , LLZTO)−polymer composite electrolyte (LLZTO/ PEO-CPE) laminated on both the anode and cathode surfaces with an ultrathin thickness of 7−10 μm by spin coating method. It is found that the LLZTO/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 59 publications
(96 reference statements)
0
32
0
Order By: Relevance
“…Above all, the proportion of inactive materials must be significantly reduced, for example, solid electrolyte separator (SES) thickness, to achieve energy densities at the cell level that exceed conventional LIB. For this purpose, Zegeye et al [112] developed an AFSSB employing ultra-thin polymer composite SSEs laminated on anode CC and cathode surfaces. The composite polymer electrolyte (CPE) with a total thickness of 15-20 µm was prepared from PEO, lithium bis (trifluoromethanesulphonyl) imide (LiTFSI) salt, and Li 6.75 La 3 Zr 1.75 Ta 0.25 O 12 (LLZTO) using a spin-coating method.…”
Section: Afssb With Composite Cathodementioning
confidence: 99%
See 1 more Smart Citation
“…Above all, the proportion of inactive materials must be significantly reduced, for example, solid electrolyte separator (SES) thickness, to achieve energy densities at the cell level that exceed conventional LIB. For this purpose, Zegeye et al [112] developed an AFSSB employing ultra-thin polymer composite SSEs laminated on anode CC and cathode surfaces. The composite polymer electrolyte (CPE) with a total thickness of 15-20 µm was prepared from PEO, lithium bis (trifluoromethanesulphonyl) imide (LiTFSI) salt, and Li 6.75 La 3 Zr 1.75 Ta 0.25 O 12 (LLZTO) using a spin-coating method.…”
Section: Afssb With Composite Cathodementioning
confidence: 99%
“…[36] Lee et al [113] achieved a favorable SES (Li 6 PS 5 Cl) thickness of 30 µm by slurry casting and subsequent pressurization in a cell. Zegeye et al [112] demonstrated a composite SES with a thickness of 15-20 µm prepared from LiTFSI in PEO and LLZTO using a spin-coating method. Schiffmann et al [256] developed 25 µm thin SES based on LLTO by tape casting and subsequent sintering.…”
Section: Cell Design and Practical Energy Densitymentioning
confidence: 99%
“…Zegeye et al used the garnet−polymer composite electrolyte (LLZTO/PEO−CPE) laminated on both the anode and cathode surface by a spin‐coating method (Figure 7c). [ 94 ] This composite polymer electrolyte (CPE) was composed of the polyethylene oxide (PEO) polymer, lithium bis(trifluoromethanesulphonyl)imede (LiTFSI) salt, and Li 6.75 La 3 Zr 1.75 Ta 0.25 O 12 (LLZTO) filler. To enhance interface compatibilities, a well‐designed LLZTO/PEO−CPE was laminated onto the anode and cathode surface, which minimized the boundary resistance.…”
Section: The Substrate Designmentioning
confidence: 99%
“…f ) Cycle performance and CE of the Cu||LLZTO/PEOÀCPE||NMC cell. Reproduced with permission [94]. Copyright 2018, American Chemical Society.…”
mentioning
confidence: 99%
“…2 This protocol also gives reliable information about the irr-CE sources that could be attributed to SEI formation, electrolyte decomposition, and dead Li formation. 16,19,23,34,35 To extract reliable information related to the irreversible reactions (irr-rxns) at the cathode surface, the cathode||Li cell configuration is an efficient protocol. Reliable information regarding the first irreversible capacity, cathode electrolyte interface (CEI), cathode degradation, and oxidative electrolyte decomposition at the cathode surface can be extracted from the cathode||Li cell configuration.…”
Section: Introductionmentioning
confidence: 99%